Inclusive Islamic Education: The Role of Religious Moderation in Transformation of Islamic Education Institutions in Riau - Juni Erpida Nasution; Bela Nurhayati; Novri Suparman (AL-ISHLAH: Jurnal Pendidikan, 2024)
The transformation of Islamic Higher Education Institutions (hereafter, PTKIS) towards quality education with a religious moderation approach in the Indragiri Hulu District, Riau Province, is crucial for meeting contemporary challenges and fostering socio-economic development. This article explores the integration of religious moderation within the PTKIS environment in the Indragiri Hulu District and the developmental direction of private PTKIS in the region adopting a religious moderation approach. Research outcomes emphasize key transformational aspects, including curriculum adjustments to incorporate religious moderation content into every lecture. This aligns with moderate Islamic values and reflects the latest developments in science and technology, aiming to enhance accessibility and educational quality, creating an innovative learning environment. PTKIS in the Indragiri Hulu District is dedicated to creating an inclusive campus that respects diversity, promotes critical thinking, and instills tolerance. Emphasizing the improvement of teaching and research quality involves applying religious moderation values in all academic activities. Modernizing campus facilities, including digital libraries and state-of-the-art laboratories, is prioritized to meet contemporary educational standards. A hidden curriculum is implemented for broad student participation. Additionally, PTKIS collaborates with local governments, communities, and the industrial sector to establish close links between education and employment, preparing graduates with practical skills for a competitive job market. The transformation of PTKIS in the Indragiri Hulu District establishes a holistic, modern educational foundation aligned with religious moderation values, contributing positively to character formation, intellectual development, and active engagement in a diverse society.